2022
DOI: 10.1038/s41598-022-10815-7
|View full text |Cite
|
Sign up to set email alerts
|

Role of trade agreements in the global cereal market and implications for virtual water flows

Abstract: Understanding the dynamics of food trade, which involves a corresponding virtual trade in environmental resources, is relevant for its effects on the environment. Among the socioeconomic factors driving the international food market, trade agreements play a significant yet poorly understood role in facilitating access to worldwide trade. Focusing on the global trade of grain from 1993 to 2015, we investigate the role of trade agreements in activating new linkages and increasing traded volumes and their environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Regarding sustainability factors, water use efficiency (WUE) shows an increasing importance in our results. For example, as pointed out in the literature 29 , trade agreements favour goods with higher water productivity. Differences between trade links covered by agreements and those not covered are amplified when focusing on blue water.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Regarding sustainability factors, water use efficiency (WUE) shows an increasing importance in our results. For example, as pointed out in the literature 29 , trade agreements favour goods with higher water productivity. Differences between trade links covered by agreements and those not covered are amplified when focusing on blue water.…”
Section: Resultsmentioning
confidence: 90%
“…For example, trade agreements play a significant role in global food trade dynamics, activating new links and increasing traded volumes. Such agreements contribute to a more stable market and carry essential environmental implications in the realm of food trade 28 , 29 . Moreover, the study of drivers in global food trade can inform efforts to promote sustainable agriculture practices, reduce waste and spoilage, and ensure equitable access to nutritious food for all 30 , 31 .…”
Section: Introductionmentioning
confidence: 99%
“…Fifthly, some scholars also explore the relationship between grain yields and rural development, poverty reduction, and the role of rural infrastructure, education, and health in improving productivity (Wang et al, 2015;Ge et al, 2018). Finally, market access and international trade are examined to understand the effects on domestic grain prices and production (Chan, 2022;Falsetti et al, 2022). This study examines the impact of the development level of ASS on grain production by analysing provincial panel data from China between 2011 and 2020, an area that has received little attention in previous research.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies have systematically analyzed VWT patterns based on multi-regional input-output models (Graham et al 2020;Islam et al 2021). In international trade, multi-regional input-output tables were constructed using global trade data, and a global VWT network was developed by combining sectoral water consumption data (Falsetti et al, 2022;Mekonnen & Hoekstra, 2020). The study found that developing countries undertake many waterintensive products, sacrificing water resources in exchange for economic rewards (Maroufpoor et al 2021).…”
Section: Introductionmentioning
confidence: 99%